Mechanical Behavior of a Twip Steel (Twinning Induced Plasticity) - Monsalve Alberto (2015)
A TWIP steel (0.65%C; 22%Mn; 0.28%Cr; 0.16%Si) was produced in the laboratory by melting, casting, hot forging and hot rolling. The relationship between mechanical twinning fraction and mechanical behavior of this steel was studied through tension tests at the following temperatures: 25, 300, 325, 350, 375 and 400°C. Fracture toughness was measured from J integral evaluation at temperatures where the principal hardening mechanism is mechanical twinning and dislocation glide (325 and 375°C respectively), for which a set of CT samples were pre-cracked by fatigue and then loaded until fracture in accordance to ASTM 1820. The plastic strain energy absorbed by each sample during crack growth was studied, correlating twinning with the mechanical response of the material, determining a decrease of plastic deformation energy around 375ºC, where the main deformation mechanism is strain hardening by dislocation glide and not mechanical twinning. Results obtained by different mechanical tests show that mechanical twinning activates in a range of stacking fault energy in the range 18 to 50 mJ/m2.